2020
DOI: 10.1007/s00432-020-03393-6
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node mapping with indocyanine green in cervical cancer patients undergoing open radical hysterectomy: a single-institution series

Abstract: Purpose To assess the rate of bilateral sentinel lymph node (SLN) detection with indocyanine green (ICG), to evaluate the sensitivity and the negative predictive value of cervical cancer patients undergoing open radical hysterectomy; to compare open versus minimally invasive SLN biopsy performance and to assess factors related to no/unilateral SLN mapping. Methods We retrospectively reviewed consecutive patients with FIGO 2018 stage IA1 with lymph-vascular space involvement to IIB and IIIC1p cervical carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
12
0
1
Order By: Relevance
“…There is accumulating evidence in the literature to support the safety and feasibility of lymphatic mapping and sentinel lymph nodes staging in cervical cancer [ 12 , 13 , 16 , 32 ]. Notwithstanding the large tumor size up to 4 cm, there is still a good detection rate of SLN reported in a few studies; The SENTICOL I (Ganglion Sentinelle dans le Cancer du Col) study showed a 92% sensitivity and 98.2% negative predictive value for node metastasis detection in patients with cervical cancer who underwent technetium-99 lymphoscintigraphy and Patent Blue injection followed by the laparoscopic lymph node mapping [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There is accumulating evidence in the literature to support the safety and feasibility of lymphatic mapping and sentinel lymph nodes staging in cervical cancer [ 12 , 13 , 16 , 32 ]. Notwithstanding the large tumor size up to 4 cm, there is still a good detection rate of SLN reported in a few studies; The SENTICOL I (Ganglion Sentinelle dans le Cancer du Col) study showed a 92% sensitivity and 98.2% negative predictive value for node metastasis detection in patients with cervical cancer who underwent technetium-99 lymphoscintigraphy and Patent Blue injection followed by the laparoscopic lymph node mapping [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Retrospectively reviewed data from five European centres have already shown ICG to be superior to 99 m technetium and blue dye with a detection rate reaching 100% and with better visualization of the bilateral lymph drainage pathways (99%) [ 34 , 35 ]. A new Italian study demonstrated that there is no significant difference in ICG SLN diagnostic performance in cervical cancer between open and minimal access surgery, with a sensitivity and negative predictive values of 83.3% and 95.0%, respectively in open access surgery, and 92.9% and 97.5%, respectively in minimal access surgery [ 13 ]. These critical results emphasize the high unmet medical need and growing demand for more data on SLN detection using ICG in open surgery for cervical cancer, in particular following the LACC-trial findings [ 20 ], which have shifted our practice towards open access with a few exemptions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations